2011
DOI: 10.1042/bj20110022
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic reduction of the secondary bile acid 7-oxolithocholic acid is mediated by 11β-hydroxysteroid dehydrogenase 1

Abstract: The oxidized bile acid 7-oxoLCA (7-oxolithocholic acid), formed primarily by gut micro-organisms, is reduced in human liver to CDCA (chenodeoxycholic acid) and, to a lesser extent, UDCA (ursodeoxycholic acid). The enzyme(s) responsible remained unknown. Using human liver microsomes, we observed enhanced 7-oxoLCA reduction in the presence of detergent. The reaction was dependent on NADPH and stimulated by glucose 6-phosphate, suggesting localization of the enzyme in the ER (endoplasmic reticulum) and dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 50 publications
(63 reference statements)
1
40
2
Order By: Relevance
“…Human 11 ␤ -HSD1 preferentially formed CDCA with minor amounts of UDCA as reported earlier ( 26 ). Canine and hamster 11 ␤ -HSD1 almost completely converted the substrate and presented similar stereoselectivity to human 11 ␤ -HSD1, thus mainly producing the 7 ␣ -hydroxylated bile acid CDCA, with minor amounts of the 7 ␤ -hydroxylated UDCA.…”
Section: Animal Experimentationsupporting
confidence: 50%
See 3 more Smart Citations
“…Human 11 ␤ -HSD1 preferentially formed CDCA with minor amounts of UDCA as reported earlier ( 26 ). Canine and hamster 11 ␤ -HSD1 almost completely converted the substrate and presented similar stereoselectivity to human 11 ␤ -HSD1, thus mainly producing the 7 ␣ -hydroxylated bile acid CDCA, with minor amounts of the 7 ␤ -hydroxylated UDCA.…”
Section: Animal Experimentationsupporting
confidence: 50%
“…Performing in vitro experiments, we recently identifi ed a novel role for human 11 ␤ -HSD1 in the metabolism of the secondary bile acid 7-oxoLCA ( 26 ). We observed that recombinant human 11 ␤ -HSD1 preferentially reduced 7-oxoLCA to the 7 ␣ -hydroxylated bile acid chenodeoxycholic acid (CDCA) and, to a lesser extent, to the 7 ␤ -hydroxylated ursodeoxycholic acid (UDCA) ( 26 ). We hypothesized that the metabolism by 11 ␤ -HSD1 might be responsible for the very low circulating levels of this secondary bile acid.…”
Section: Impact Of Bile Acids On the Interconversion Of Glucocorticoimentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported that 7-oxo-lithocholic acid (7-oxo-LCA), a bacterial metabolite of CDCA, acts as a competitive inhibitor of human hepatic 11b-hydroxysteroid dehydrogenase-1 (11b-HSDH1). 93 Hepatic 11b-HSDH1 recognizes 7-oxo-LCA as a substrate and reduces this bacterial metabolite back to CDCA. 94 However, in the process, 7-oxo-LCA inhibits cortisone reduction back to active cortisol.…”
Section: Pathophysiological Relevance Of Secondary Bile Acids To Hostmentioning
confidence: 99%